2017
DOI: 10.4269/ajtmh.16-0917
|View full text |Cite
|
Sign up to set email alerts
|

Rocky Mountain Spotted Fever and Pregnancy: Four Cases from Sonora, Mexico

Abstract: We present a series of four pregnant women with Rocky Mountain spotted fever (RMSF) that occurred in Sonora, Mexico, during 2015-2016. Confirmatory diagnoses were made by polymerase chain reaction or serological reactivity to antigens of by using an indirect immunofluorescence antibody assay. Each patient presented with fever and petechial rash and was treated successfully with doxycycline. Each of the women and one full-term infant delivered at 36 weeks gestation survived the infection. Three of the patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
0
8
0
2
Order By: Relevance
“…Se sabe que, en estas dos enfermedades, están indicados antibióticos específicos que reducen la letalidad si se suministran de manera oportuna, idealmente en los primeros cinco días de la enfermedad. En algunos estudios se ha demostrado que la resolución de la enfermedad obedece a una intervención terapéutica rápida, incluso en presentaciones atípicas ( 20 , 21 ).…”
Section: Discussionunclassified
“…Se sabe que, en estas dos enfermedades, están indicados antibióticos específicos que reducen la letalidad si se suministran de manera oportuna, idealmente en los primeros cinco días de la enfermedad. En algunos estudios se ha demostrado que la resolución de la enfermedad obedece a una intervención terapéutica rápida, incluso en presentaciones atípicas ( 20 , 21 ).…”
Section: Discussionunclassified
“…All of the mothers survived and one child born by SVD at 36 weeks had an uncomplicated course. Three women in the first trimester had spontaneous abortions (41). The authors identify 10 patients in the literature including their four patients.…”
Section: Rickettsia Rickettseiimentioning
confidence: 99%
“…A case series of four patients in Mexico treated with doxycycline for RMSF had bad outcomes, with three mothers having spontaneous abortions in the first trimester, the fourth was a full-term spontaneous vaginal delivery (SVD). 144 The authors identified 10 cases in the literature including their four patients. Doxycycline was used in five cases, chloramphenicol in three and amoxicillin in two.…”
Section: Rickettsia Rickettseiimentioning
confidence: 99%